How Do Millennial and Z Generations Make Investment Decisions? A Case Study From Makassar City - Musa, Muhammad Ichwan; Aslam, Annisa Paramaswary; Aswar, Nurul Fadilah; Syahrul, Khaidir; Abadi, Rahmat Riwayat (PT. Maju Malaqbi Makkarana, 2023)
This study purpose to support the Indonesia’s government program to become a developed and prosperous country. The sample for this study the millennial generation and Z generation who live Makassar City and have total wealth or investment around IDR 70 million. We use this generations because the next generation has an important role to build and develop the finance sector in Indonesia and will support to become a developed country. The results show that financial literacy, income and financial behavior significantly positive with investment decisions. It is mean that good financial literacy, higher income, and the well financial behaviour will improve the quality of investment decisions.